Super resolution imaging reconstruction reveals that gold standard methods may not correctly conclude neural/brain functional recovery. (April 2023) - Huang, Weifeng; Hua, Chen; Guo, Yan; Gao, Wenwei; Li, Yingchuan; Zheng, Yuanyi
Abstract: The status of cerebral perfusion and its restoration level play a vital role in the prognosis and clinical decision making of many neurosurgical diseases. As such, gold standard methods including CT, MR and ICP monitoring, which can indicate and measure cerebral perfusion and restoration, have been widely adopted to evaluate whether or not a patient has recovered from neurofunctional disabilities. This robust combination of methods, however, is confronted with a growing number of contradictions in recent years due to its inability to measure the status of cerebral reperfusion in microvasculature level, even though this has been shown to determine neurofunctional restoration as well or even better. To this date, nevertheless, we have very limited imaging methods that could evaluate human cerebral microperfusion both safely and accurately under most neurosurgical conditions. We herein report a new method of acquiring a patient's cerebral microperfusion status noninvasively which could display the precise distribution of microvasculature in deep cerebral regions with a resolution of ∼30 µm, using everyday bed-side ultrasonography combined with a computerized super-resolution reconstruction algorithm. Using this imaging modality, we found that a patient's cerebral microperfusion might not be improved by some routine administrations even though the gold standard method had yielded the opposite conclusions. Our imaging modality retains the safe, portable feature of ordinary ultrasonography while possesses the extraordinary super-resolution nature, which enables an efficient, precise diagnosis of cerebral perfusion. Most importantly, the super resolution nature of this method may also facilitate early-stage evaluation of a patient's neurofunctional restoration level and avoid overoptimistic conclusions from conventional angiography or ICP monitoring. Graphical Abstract: ga1 Highlights: Confirm the possibility of SRUS technique for brain microcirculation imaging on patients. Report relationship between microcirculation and ICP, helpful for clinical evaluation & treatment of stroke patients. Improve brain imaging quality by 30 fps sonography other than special machine of ∼1000 fps, useful to clinical translation.